Atomic Layer Deposition for Membranes, Metamaterials, and Mechanisms. Issue 29 (30th May 2019) - Dorsey, Kyle J.; Pearson, Tanner G.; Esposito, Edward; Russell, Sierra; Bircan, Baris; Han, Yimo; Miskin, Marc Z.; Muller, David A.; Cohen, Itai; McEuen, Paul L.
Abstract: Bending and folding techniques such as origami and kirigami enable the scale‐invariant design of 3D structures, metamaterials, and robots from 2D starting materials. These design principles are especially valuable for small systems because most micro‐ and nanofabrication involves lithographic patterning of planar materials. Ultrathin films of inorganic materials serve as an ideal substrate for the fabrication of flexible microsystems because they possess high intrinsic strength, are not susceptible to plasticity, and are easily integrated into microfabrication processes. Here, atomic layer deposition (ALD) is employed to synthesize films down to 2 nm thickness to create membranes, metamaterials, and machines with micrometer‐scale dimensions. Two materials are studied as model systems: ultrathin SiO2 and Pt. In this thickness limit, ALD films of these materials behave elastically and can be fabricated with fJ‐scale bending stiffnesses. Further, ALD membranes are utilized to design micrometer‐scale mechanical metamaterials and magnetically actuated 3D devices. These results establish thin ALD films as a scalable basis for micrometer‐scale actuators and robotics. Abstract : Atomic layer deposition enables fabrication of microstructures with extraordinarily low stiffness at nanometer‐scale thickness. Low‐stiffness films of SiO2 and Pt are employed to miniaturize mechanical metamaterials and mechanisms that can withstand repeated actuation and extreme deformation. Sensitive magnetic actuators are presented as an example application of this fabrication platform.